2002
DOI: 10.4049/jimmunol.169.1.315
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype and Regulation of Persistent Intracerebral T Cells in Murine Toxoplasma Encephalitis

Abstract: Toxoplasma gondii is a parasite causing asymptomatic, persistent encephalitis. Protective CD4 and CD8 T cells are recruited to and accumulate in the brain in acute Toxoplasma encephalitis (TE), with slowly decreasing numbers in chronic TE. It is unclear how the size of the intracerebral T cell pool is regulated. Conceivably, permanent recruitment, proliferation, and apoptosis may be involved. We observed that in murine TE recruitment of T cells to the brain was terminated in chronic TE. In vivo 5-bromo-2′-deox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
30
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 31 publications
5
30
0
Order By: Relevance
“…Thus, intracerebral CD8 T cells specific for a secreted Ag of tachyzoite were not eliminated from the brain in chronic TE, i.e., when the parasite persists as bradyzoites within cysts. The persistence of these CD8 T cells is consistent with the observation that intracerebral T cells form a stable cell pool in chronic TE, which is only slowly downsized by a low level of apoptosis (7). Because ␤-gal-specific CD8 T cells were functionally active and rapidly produced IFN-␥ (the major cytokine in resistance against T. gondii (33)) upon peptide restimulation and also killed peptide-pulsed APCs, they appear to play an important role in the control of intracerebral parasites in acute and chronic TE.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Thus, intracerebral CD8 T cells specific for a secreted Ag of tachyzoite were not eliminated from the brain in chronic TE, i.e., when the parasite persists as bradyzoites within cysts. The persistence of these CD8 T cells is consistent with the observation that intracerebral T cells form a stable cell pool in chronic TE, which is only slowly downsized by a low level of apoptosis (7). Because ␤-gal-specific CD8 T cells were functionally active and rapidly produced IFN-␥ (the major cytokine in resistance against T. gondii (33)) upon peptide restimulation and also killed peptide-pulsed APCs, they appear to play an important role in the control of intracerebral parasites in acute and chronic TE.…”
Section: Discussionsupporting
confidence: 88%
“…with PruS1SPLACZ, when a significant number of leukocytes including CD8 T cells had already been recruited to the brain (Ref. 7 and present study, data not shown), 2.0 and 4.2% of total CD8 T cells in the spleen and the brain stained positively with L d /␤-gal 876 -884 tetramer, respectively (Fig. 4, A and B).…”
Section: Impact Of Stage-specific Ag Expression For the Induction Of supporting
confidence: 62%
See 2 more Smart Citations
“…Given that cytokines could act in a paracrine fashion to stimulate other cell types, such as macrophages and astrocytes, to control T. gondii growth (11-13, 25, 26) it is conceivable that CD8 T cells could provide protection without the need to stably contact invaded host cells. Studies of leukocytes isolated from brains of chronically infected mice have provided important information about CD8 T cells (24,(27)(28)(29); however the nature of interactions between CD8 T cells and brain APCs has not yet been explored.…”
mentioning
confidence: 99%